Metal-ceramic diffusion barrier nanocomposite coatings on nickel based superalloys for corrosion and high temperature oxidation resistance. Issue 21 (1st November 2022) - Kirubaharan, A.M. Kamalan; Kuppusami, P.; Ghosh, Chanchal; Priya, R.; Ningshen, S.; Kumar, D. Dinesh; Divakar, R.
Abstract: Ceramic diffusion barrier coatings are inevitable in high temperature aerospace and nuclear applications to protect superalloys from oxidation and hot corrosion. Compositionally graded coating (CGC) of Ni-YSZ with five layers was deposited on an Inconel-690 substrate through electron beam physical vapor deposition (EBPVD) method. After heat treatment, the phase formation and crystallite determination in each layer of the CGC were studied by X-ray diffraction. Pulsed radio frequency glow discharge optical emission spectroscopy (RF-GDOES) showed outward diffusion of Ni towards the surface of the CGC. High resolution transmission electron microscopy (HRTEM) studies of the cross-sectional region of the heat-treated coating at 1273 K revealed no secondary phases within the coating as well as at substrate-coating interface. The corrosion behavior of Ni-YSZ coating under 3 M HNO3 medium showed that the heat-treated CGC of Ni-YSZ exhibited better corrosion resistance due to the formation of NiO than as-deposited Ni-YSZ coating.